Good Governance and Anthropology on Preventing HIV/AIDS in Gondanglegi District of Malang - Hipolitus Kristoforus Kewuel; Sri Herminingrum; Siti Zurinani (Institute of Research and Community Service, University of Brawijaya)
Using ethnographic as qualitative approach in extracting data, the aim of this study is to reveal the causing factors of high-rate of HIV/AIDS epidemic in Gondanglegi District of Malang. It is also to disclose the extent of Malang regency administration has sought to overcome this social phenomenon. Thus, the depth information about the cause of high-rate HIV/AIDS and preventive efforts can be used to conduct mitigation measures in the future. The results showed two points. First, the causing factors of high HIV/AIDS epidemic in Gondanglegi District of Malang are the low levels of economy, high levels of migration, and the growing influence of lifestyle among the younger generation. Secondly, with the Regional AIDS Commissions (KPAD), Malang Regency Government has made prevention efforts in cooperation with NGO Paramitra and NGO Sadar Hati. One of the main programs is Warga Peduli AIDS (WPA). Through this program, the Local Government is responsible to provide the medical facilities at the health centers that have been appointed. Meanwhile, the NGO responsibility is to build the awareness of treatment and check-up, especially for the high risk communities. Keywords: good governance, anthropology, hiv/aids preventive efforts